Pathophysiologically relevant bisphenol S exposure accelerates aging by disrupting brown adipose tissue–regulated energy metabolism - Man Zhu; Ru Wang; Wei Yi; Beiyi Wu; Zhizhong Deng; Zheng Zhang; Chen Wang; Dingkun Zhang; Tongtong Zhang; Xue Wen (Proceedings of the National Academy of Sciences, 2025)
Bisphenol A (BPA) substitutes are widely used as food contact materials and consumer products, while the effects of pathophysiologically relevant concentrations of BPA substitutes on aging remain unclear. In this study, we used Caenorhabditis elegans ( C. elegans ) to investigate the effects of five BPA substitutes [bisphenol S (BPS), bisphenol B, bisphenol F (BPF), tetramethyl BPF, and 4,4′-(Perfluoropropane-2,2-diyl)diphenol] at pathophysiologically relevant exposure levels during aging and examined the underlying mechanisms using a mouse model. Our results indicated that, among the five BPA substitutes, exposure to pathophysiologically relevant concentrations of BPS (300, 450, and 600 nM) accelerated aging in C. elegans . In mice, exposure to a pathophysiologically relevant concentration of BPS (125 μg/kg/day, from 4 to 20 mo of age) similarly reduces the life and health span and accelerates aging phenotypes in multiple tissues. Further investigations demonstrated that long-term BPS exposure resulted in a significantly higher accumulation of BPS in brown adipose tissue (BAT) than in other organs. RNA sequencing analysis of BAT revealed that BPS accelerates BAT aging through multiple pathways. Importantly, transplantation of BAT from BPS-exposed mice into BPS-naive mice accelerated aging in recipients. Conversely, transplantation of BAT from unexposed mice into BPS-exposed mice significantly improved their metabolic status and delayed aging. These findings elucidate the impact of pathophysiologically relevant concentrations of BPS on the aging process and suggest that these effects are likely mediated through the disruption of BAT function.